Social Media Image Construction and Communication of Sports Athletes: – Take Eight Chinese Table Tennis Athletes on Weibo as an Example - Li, Ruolin (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of social media, it has become more and more a distinctive phenomenon for sports athletes to present themselves and spread sports culture through operating personal social media accounts. As the national sport of China, table tennis has long enjoyed widespread attention, and the athletes are also the focus of the public. In this regard, this paper selected eight Chinese table tennis athletes in different growth periods in a balanced manner according to the demographic approach. With the content and text analysis methods, the paper collects data and text from their social media accounts represented by Weibo, and analyzes the content and effects from aspects of sports communication, health communication, brand communication, social value communication and entertainment daily communication. After analyzing the current operation and exposed shortcomings of the personal social media of sports athletes represented by them, the paper puts forward three feasible suggestions: “build a good media image, convey positive energy actively,” “raise the awareness of media management, explore the possibilities of cross-border” and “enhance the ability of media operation, create differentiated personalities,” to contribute media power to the in-depth implementation of the "Healthy China" Initiative and the development of China’s sports industry.